INTERNAL CONTROL AND INTERNAL AUDIT ROLE IN THE MANAGEMENT - Popović, Slobodan M; Mijić, Ranko; Grublješić, Željko (International Journal of Economic Practice and Policy, 2014)
Due to the highly dynamic changes in the market, especially in the capital markets, capital owners and investors need a reliable and independent opinion on the financial statements of companies that are the subject of their interest. In conditions that are characterized by high uniformity of heterogeneous financial statements, company’s management looks for ways to establish better control of the company, which is a long and continuous process. An internal control and internal audit of the company’s business and operations provide a full support in that attempt. The paper presents empirical research on the example of Sierpinski triangle (also, Sierpinski gasket) shown in the form of a diagram. In addition, the paper presents the elements of the management approach to internal control and the basic views on internal audit that can be applied to operational management of the majority of medium-sized and large enterprises. A large number of displayed elements coexist in mutual respect and together make a strong and cohesive whole. It is important to note that there is no such system of internal control and internal audit when perfect results are ensured to protect the company from unwanted effects.